Branded content versus product placement. Visibility, perception and consumer´s brand recall - Formoso Barro, María Josefa; Sanjuán Pérez, Antonio; Martínez Costa, Sandra (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2016)
Product placement has been long efficiency, despite being one of the most controversial advertising modalities for its invasive methods. However, the branded content has always been appreciated among advertising professionals, but it remains to get a correct measurement of its effectiveness. This article is a result of an experimental research comparing advertising formulas of product placement and branded content from the same advertiser, in order to identify which one of both methods is more efficient for product visibility, brand recall and emotional perception improvement.To do that, a qualitative study in two different user groups was made with eye tracking and some open and closed questions. Each group was exposed to one of the advertising methods. The analysis results indicate that the values of visibility and brand recall differ from those on the emotional and subjective perception depending on the advertising method used.